(untitled) - Bùi, Huệ Phương (Cần Thơ, 2018)
The current study was conducted, aiming to achieve two research aims. Firstly, the study investigated the extent to which the use of picture description affects students’ coherence in speaking. Secondly, the study is also aimed at exploring students’ attitudes towards the use of picture description in speaking sessions.
Keywords: Tiếng Anh,English language; Nói tiếng Anh,Nghiên cứu,Spoken English,Research